Third-generation smallpox vaccine strain-based recombinant vaccines for viral hemorrhagic fevers. Issue 41 (1st October 2021) - Yoshikawa, Tomoki
Abstract: Vaccinia virus has been used as a smallpox vaccine. Now that smallpox has been eradicated, the vaccinia virus is expected to be used as a bioterrorism countermeasure and a recombinant vaccine vector for other infectious diseases, such as viral hemorrhagic fevers. Many vaccinia virus strains were used as smallpox vaccines in the smallpox eradication campaign coordinated by the World Health Organization. These strains can be classified into generations, according to the history of improving production methods and efforts to reduce the adverse reactions. Significantly, the third-generation of smallpox vaccine strains, which include modified vaccinia Ankara (MVA) and LC16m8, are currently popular as recombinant vaccine vectors due to their well-balanced safety and immunogenicity profiles. The present review firstly focuses on the characteristics of the smallpox vaccine generations. The historical background of the development of the third-generation smallpox vaccine strains is detailed, along with the history of the transition of the vaccinia virus generation used as vectors for hemorrhagic fever vaccines to the third generation. Among the vaccinia viruses, MVA is currently the most commonly used vector for developing hemorrhagic fever vaccines, including dengue fever, yellow fever, Ebola viral disease, Lassa fever, Rift Valley fever, and Crimean-Congo hemorrhagic fever. LC16m8 is a vaccine candidate for severe fever with thrombocytopenia syndrome. The current status and recent advances in the development of these hemorrhagic fever vaccines using third-generation vaccinia strains are discussed.